Correction: Influence of silk–silica fusion protein design on silica condensation in vitro and cellular calcification. Issue 114 (6th December 2016) - Plowright, Robyn; Dinjaski, Nina; Zhou, Shun; Belton, David J.; Kaplan, David L.; Perry, Carole C.
Abstract : Correction for 'Influence of silk–silica fusion protein design on silica condensation in vitro and cellular calcification' by Robyn Plowright et al., RSC Adv., 2016, 6, 21776–21788.